Prolonged dopamine D3 receptor stimulation promotes dopamine transporter ubiquitination and degradation through a PKC-dependent mechanism. (March 2021) - Luis-Ravelo, Diego; Fumagallo-Reading, Felipe; Castro-Hernandez, Javier; Barroso-Chinea, Pedro; Afonso-Oramas, Domingo; Febles-Casquero, Alejandro; Cruz-Muros, Ignacio; Salas-Hernandez, Josmar; Mesa-Infante, Virginia; Rodriguez-Nuñez, Julia; Gonzalez-Hernandez, Tomas
Graphical abstract: Highlights: D3R regulates DAT in a biphasic way. Acute D3R activation increases DAT expression in the plasma membrane and DA uptake. Prolonged D3R activation promotes DAT phosphorylation and ubiquitination. After prolonged D3R activation, DAT is degraded, reducing DA uptake. Abstract: The dopamine transporter (DAT) is a membrane glycoprotein in dopaminergic neurons, which modulates extracellular and intracellular dopamine levels. DAT is regulated by different presynaptic proteins, including dopamine D2 (D2 R) and D3 (D3 R) receptors. While D2 R signalling enhances DAT activity, some data suggest that D3 R has a biphasic effect. However, despite the extensive therapeutic use of D2 R/D3 R agonists in neuropsychiatric disorders, this phenomenon has been little studied. In order to shed light on this issue, DAT activity, expression and posttranslational modifications were studied in mice and DAT-D3 R-transfected HEK cells. Consistent with previous reports, acute treatment with D2 R/D3 R agonists promoted DAT recruitment to the plasma membrane and an increase in DA uptake. However, when the treatment was prolonged, DA uptake and total striatal DAT protein declined below basal levels. These effects were inhibited in mice by genetic and pharmacological inactivation of D3 R, but not D2 R, indicating that they are D3 R-dependent. No changes were detected in mesostriatal tyrosine hydroxylase (TH) protein expression and midbrain TH and DAT mRNAs, suggesting that the dopaminergic system is intact and DAT is posttranslationally regulated. The use of immunoprecipitation and cell surface biotinylation revealed that DAT is phosphorylated at serine residues, ubiquitinated and released into late endosomes through a PKCβ-dependent mechanism. In sum, the results indicate that long-term D3 R activation promotes DAT down-regulation, an effect that may underlie neuroprotective and antidepressant actions described for some D2 R/D3 R agonists.